2017
DOI: 10.1590/1519-6984.166631
|View full text |Cite
|
Sign up to set email alerts
|

Gill metazoan parasites of the spotted goatfish Pseudupeneus maculatus (Ostheichthyes: Mullidae) from the Coast of Pernambuco, northeastern Brazil

Abstract: This study evaluated the parasite fauna on the gills of spotted goatfish Pseudupeneus maculatus captured in the dry and rainy seasons in the coast of the State of Pernambuco, Brazil. Eight parasite species were identified belonging to the following taxa: Monogenea (Haliotrema caraïbensis, Haliotrema caballeroi and Haliotrema golvani); Crustacea (Rocinela signata, Hamaticolax scutigerulus and Caligidae gen. sp.) and Cestoda (Nybelinia indica and Pseudolacistorhynchus noodti). The most prevalent parasites were: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…The parasites are related to aspects of the biology of their hosts, such as diet and migration (Cardoso et al, 2018). For this reason, marine fish are paratenic, intermediate and definitive hosts of a wide range of external and internal parasites Luque et al, , 2017Cardoso et al, 2018). The diversity of parasites found in the present study is greater than that reported for P.…”
Section: Resultscontrasting
confidence: 54%
See 2 more Smart Citations
“…The parasites are related to aspects of the biology of their hosts, such as diet and migration (Cardoso et al, 2018). For this reason, marine fish are paratenic, intermediate and definitive hosts of a wide range of external and internal parasites Luque et al, , 2017Cardoso et al, 2018). The diversity of parasites found in the present study is greater than that reported for P.…”
Section: Resultscontrasting
confidence: 54%
“…(Schlacher et al, 2007), which favors the dispersion of parasites (Feist and Longshaw, 2008). The parasites are related to aspects of the biology of their hosts, such as diet and migration (Cardoso et al, 2018). For this reason, marine fish are paratenic, intermediate and definitive hosts of a wide range of external and internal parasites Luque et al, , 2017Cardoso et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Amazon, several factors influence the parasitic load of fish, such as seasonality, abiotic and biotic factors in aquatic environment water, and host ecology (NEVES et al, 2013). The diversity and ecological function of the parasites in an ecosystem can be used as tools for a better understanding of the biosphere, as well as the parasitic indexes that support parasite-host relationship analysis (TAVARES-DIAS et al 2014CARDOSO et al, 2018. TAKEMOTO et al (2004) stated that all fish hosted at least one species of parasite and the location of the parasites may vary, where no organ is free from parasitism, but one organ may have more parasites than another organ.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have reported that gills are one of the most parasitized organs (CARDOSO et al, 2018;JERÔNIMO et al, 2014, GONÇALVES et al, 2014, VENTURA et al, 2013, SANTOS et al 2013OLIVEIRA et al, 2016). Gills are easily damaged by parasitic infections, being the first organ in contact with the external environment.…”
Section: Introductionmentioning
confidence: 99%